How frontline employee experience of work and their intentions to stay or leave in the current role have been changed in the labour market under the current situation of COVID-19 in the catering industry in Nottingham - An, Tianyi (2020)
Abstract This research aims to examine what has been changed in the catering industry after the spread of the coronavirus in Nottingham and how these changes affect catering employees’ retention or turnover. This qualitative research expected to gain an in-depth understanding of catering industry employees; as the changes in this industry were significant, we did not make a hypothesis and seek to explore the answers of the strongest influencers that affect catering industry employees’ job satisfaction, organisational commitment and turnover intention from the participants’ comments. Firstly, we found that the catering industry employees’ lives and income changed during the lockdown. Employees had more time for themselves as they had to follow the self-isolated policy, which improved their well-being. Financially, catering industry employees received support from the government, which was 80% of the average weekly wages. The effect of this government scheme increased employee retention in the catering industry. Some organisation that made extra support for their employees during the lockdown received high reciprocity from employees when they reopened. After the lockdown, the slump of job vacancies in the labour market slashed actual employees’ withdrawal decisions. Catering industry employees’ workload slightly increased after the lockdown due to the impact of the coronavirus; however, no evidence shows the observable effect of this change. Moreover, we listed the most significant factors that affect the catering industry employee’s job satisfaction and organisational commitment. The typical concerns are organisational commitment, person fit, employee development, motivators, employee relations and employee well-being. We failed to find different influencers between shops that provide both indoor and outdoor service and those that offer indoor service as our assumption. However, differences were explored between professional and student employees. As professionals have more family problems and financial issues, their concerns for the job are monetary wages and support. Students seek a balance between work and study; therefore, excellent fringe pays, flexibility and promotion systems are more attractive to students. According to the findings, this research suggests that apart from design pay package wisely (e.g. adding discounts, set sales target), organisations in the catering industry should also pay attention to employees’ emotional attachment. We also confirmed the social exchange theory and reciprocity theory are commonly existing in the catering industry. Therefore, the more effort catering industry organisations paid for their employees, the more return they can obtain from the employees.